TINJAUAN YURIDIS PENGGUNAAN SURAT KUASA JUAL TERHADAP PENJUALAN OBJEK HAK TANGGUNGAN DALAM PENYELESAIAN KREDIT MACET - Alfis Setyawan (Program Studi Ilmu Hukum Universitas Maritim Raja Ali Haji, 2016)
Act No. 4 Year 1996 On Amenability Rights, did not recognize the selling power of attorney known is the agreement between the creditor and the debtor to sell the object of a security interest is under the hand as efforts to resolve the bad credit borrowers, the agreement between the creditor and the debtor agreed after the occurrence of bad loans by the debtor. Use of the selling power of attorney by the creditor for the sale of objects Amenability Right are not in accordance with the provisions of Act No. 4 Year 1996 On Amenability Rights, the lender and the buyer objects encumbrance not get legal protection, the purchase agreement does not meet the requirements of the agreement validity requirements as stipulated in Article 1320 of the Civil Code. Keywords: Selling Power of Attorney, amenability right, credit Surat kuasa jual yang dibuat dan ditanda-tangani oleh kredit dengan debitur pada saat pencairan kredit atau pada saat penandatanganan perjanjian kredit bertetangan atau tidak dikenal dalam Undang-Undang No 4 Tahun 1996 tentang Hak Tanggungan, artinya surat kuasa jual tersebut tidak mempunyai kedudukan hukum berdasarkan Undang-Undang Nomor 4 Tahun 1996 tentang Hak Tanggungan. maka kreditur dan pembeli barang pembatas tidak mendapatkan perlindungan hukum, perjanjian pembelian Tidak memenuhi persyaratan persyaratan validitas perjanjian sebagaimana diatur dalam Pasal 1320 KUH Perdata. Kata kunci: Surat Kuasa Jual, Hak Tanggungan, Kredit